Forecasting the development of antimicrobial resistance of S. aureus - Shemetov, Oleh; Faustova, Mariia; Perepelova, Tetiana; Balia, Hennadii; Pavlish, Ihor; Loban', Galina (Frontiers in Oral Health, 2025)
Today, about 15.0% of odontogenic pathology is caused by Staphylococcus aureus (S. aureus). The aim of the study was to predict the development of antimicrobial resistance of S. aureus based on retrospective data.MethodsA total of 425 patients undergoing treatment for odontogenic infectious diseases of the facial area during 2019–2023 were involved in the study. The object of the study was 106 clinical isolates of S. aureus that were isolated and identified from patients. Determining the sensitivity of the obtained isolates to antimicrobial drugs was carried out using Vitek antimicrobial susceptibility testing (Biomerioux, France) and analyzed according to the breackpoint tables of the EUCAST. Prediction of the development of antimicrobial resistance of S. aureus to various antibiotics was carried out on the basis of the received sensitivity data of the studied isolates in 2019–2023 using the exponential smoothing method.ResultsThe antimicrobial resistance of S. aureus isolates to various antibiotics changed annually during 2019–2023. The level of resistance of S. aureus isolates to benzylpenicillin wavered between 40%–50% from 2019 to 2023 with the trend of an 18.0% increase over the next five years. A uniform plateau of antimicrobial resistance of S. aureus to cefoxitin is predicted at the level of 32.0% during 2024–2028. We recorded the highest portions of S. aureus resistant to norfloxacin (33.3%) and ciprofloxacin (16.7%) in 2023 with prediction of its increasing in the next five years within the range of 20.0%. It was established that S. aureus may reach 100.0% resistance to gentamicin in 2027. According to exponential smoothing, the level of S. aureus resistance to amikacin will increase by 22.7% over the next five-year period. Moreover, representatives of this species of bacteria can develop complete (100.0%) resistance to tetracycline as early as 2027.ConclusionsMathematical prediction of the development of antimicrobial sensitivity of S. aureus isolates showed a high probability of its development to antibiotics of all groups in the next five years.